Collection management in 21st century : questioning in the Croatian context - Vujić, Žarka (Array, 2021)
This paper promotes a concept of a museum collection management and the related policy by which it is expressed. Collecting and deaccessioning (as essential activities of collections development), loans and accessibility - in international and Croatian museum practice - are also analyzed. In the end, the paper advocates the establishment of a national association of museums that could serve, together with other support points, a purpose of a professional gathering around topics on collection management.